2015
DOI: 10.1039/c5ra10638a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a photocrosslinkable chitosan–gelatin hydrogel aimed for tissue regeneration

Abstract: In the area of tissue engineering different approaches have been studied, so far, for promoting regeneration or replacement of damaged tissues. Among the different materials developed, hydrogels, due to their biocompatibility and similarities with the native extracellular matrix, have emerged as suitable candidates for being used for different therapeutic purposes. Herein, photocrosslinkable hydrogels, composed by chitosan methacrylamide (ChMA) and gelatin methacrylamide (GelMA) were crosslinked by ultraviolet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 83 publications
3
64
0
1
Order By: Relevance
“…All the samples were mounted on a diamond window and the spectra were recorded using a Nicolet iS10 FTIR spectrophotometer (Thermo Scientific, Waltham, MA, USA). In order to compare the spectra of individual components with those of the produced hydrogels, all the raw components used for hydrogel production were also analyzed [31].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…All the samples were mounted on a diamond window and the spectra were recorded using a Nicolet iS10 FTIR spectrophotometer (Thermo Scientific, Waltham, MA, USA). In order to compare the spectra of individual components with those of the produced hydrogels, all the raw components used for hydrogel production were also analyzed [31].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…) and methacrylamide chitosan (13 in Fig. ), were also proposed . However, formic acid or acetic acid was used as a solvent in this reaction condition, which could result in degradation of CS molecular chain to make final hydrogels relatively weaker.…”
Section: Synthesis Of Photoactive Cs Macromersmentioning
confidence: 99%
“…For UV photopolymerization, a common photoinitiator is Darocur 2959, which is selected due to its solubility in water and a reduced cytotoxic effect for different cell types . When Darocur 2959 is exposed to UV light, free radicals (benzoyl and ketyl) are generated and further attach the alkene groups of photoactive macromers to form intermolecular covalent bonds, leading to formation of hydrogel network that is chain growth mechanism of photopolymerization. Based on this mechanism, many photocrosslinked CS hydrogel systems were prepared.…”
Section: Photocrosslinking Processes Based On Photoactive Cs Macromersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels have found extensive applications in diverse engineering and biomedical territories, such as flexible electronics, tissue regeneration, and drug delivery . Accumulating evidence has shown that the 3D shape and size of hydrogels are vital in these applications .…”
Section: Introductionmentioning
confidence: 99%